2022
DOI: 10.1136/jitc-2021-003717
|View full text |Cite
|
Sign up to set email alerts
|

Combination of ultrasound-based mechanical disruption of tumor with immune checkpoint blockade modifies tumor microenvironment and augments systemic antitumor immunity

Abstract: BackgroundDespite multimodal adjuvant management with radiotherapy, chemotherapy and hormonal therapies, most surgically resected primary breast cancers relapse or metastasize. A potential solution to late and distant recurrence is to augment systemic antitumor immunity, in part by appropriately presenting tumor antigens, but also by modulating the immunosuppressive tumor microenvironment (TME). We previously validated this concept in models of murine carcinoma treated with a novel predominately microcavitatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…As they were used in mouse neuroblastoma, immune escape blockade using aPD-L1 and mAb was implemented after HIFU ablation, and they cooperatively caused the potent anti-tumor immune responses of the whole body and reduced the recurrence and metastasis of advanced tumors. [120,125] Similar results were obtained in the mouse pancreatic cancer model. [126] PEI-PLGA-NaHCO 3 -NPs developed by the Wang et al showed an effective tumor-targeting effect in the 4T1 breast cancer model, which was much preferable for enhancing HIFU treatment.…”
Section: Nanobiotechnology-enhanced Hifu Ablation For Activating Immu...supporting
confidence: 76%
“…As they were used in mouse neuroblastoma, immune escape blockade using aPD-L1 and mAb was implemented after HIFU ablation, and they cooperatively caused the potent anti-tumor immune responses of the whole body and reduced the recurrence and metastasis of advanced tumors. [120,125] Similar results were obtained in the mouse pancreatic cancer model. [126] PEI-PLGA-NaHCO 3 -NPs developed by the Wang et al showed an effective tumor-targeting effect in the 4T1 breast cancer model, which was much preferable for enhancing HIFU treatment.…”
Section: Nanobiotechnology-enhanced Hifu Ablation For Activating Immu...supporting
confidence: 76%
“…Cells were washed with PBS, stained with LIVE/DEAD Fixable Aqua Dead Cell Stain Kit (Thermo Fisher Scientific, Rockford, Illinois, USA), and followed by intracellular staining and/or cell surface staining as previously described. 22 23 26 Detailed staining methods are shown in online supplemental methods . Cells were acquired by LSRII flow cytometer (BD Biosciences, San Jose, California, USA) and analyzed by FlowJo software IX (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…Mouse IFN-Îł ELISPOT assays (Mabtech, Cincinnati, Ohio, USA) were done according to the manufacturer’s instructions as previously described. 22 27 Overlapping HER2 or HER3 mixed peptides (JPT Peptide Technologies, Berlin, Germany) or OVA257-264 (SIINFEKL) peptide were used to detect anti-HER2, anti-HER3 or anti-OVA cellular responses. HIV peptide mix (BD Bioscience) was used as a negative control of the assay.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations